Interaction of Pseudomonas solanacearum Lipopolysaccharide and Extracellular Polysaccharide with Agglutinin from Potato Tubers - Duvick, Jonathan P. (1984)
In vitro binding assays were used to study the possible role of a cell wall agglutinin in the attachment to plant cell walls of avirulent strains of the wilt pathogen, Pseudomonas solanacearum. In a nitrocellulose filter assay, radioactively labeled lipopolysaccharide (LPS) from the virulent strain, K60, and the avirulent strain, B1, and extracellular polysaccharide (EPS) from K60 were bound quantitatively by the agglutinin extracted from Katahdin potato tubers. The LPS from B1 had significantly greater agglutinin-binding affinity than that from K60 but not after treatment with deoxycholate, which improved solubility. Highly purified chitotetraose did not inhibit binding of K60 LPS to agglutinin, but binding was inhibited by EPS as well as by diverse anionic polymers (DNA, dextran sulfate, xanthan). Binding of agglutinin to EPS and LPS was inhibited at ionic strengths greater than 0.03 and 0.15 M, respectively. It was concluded that electrostatic charge-charge interactions could account for binding of LPS and EPS to potato agglutinin.